2012
DOI: 10.5402/2012/298098
|View full text |Cite
|
Sign up to set email alerts
|

Coloured Filters Enhance the Visual Perception of Social Cues in Children with Autism Spectrum Disorders

Abstract: Coloured filters have been found to reduce visual distortion of text in children with autism spectrum disorders (ASD). We investigated the effect of the overlays on the “mind in the eye” task in children with ASD and controls matched for age, gender, and nonverbal IQ. Children were shown photographs of the periocular region of various faces and were asked to judge which emotion was being expressed in the eyes. In children with ASD, the perception of the emotion was significantly improved when the photograph wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…This study found that self‐selected colored tints improved judgments of the intensity of facial expressions for individuals with ASD but not for TD individuals, in line with the findings of Ludlow et al []. In contrast to TD individuals, whose judgments were (non‐significantly) poorer when colored tints were added to faces, individuals with ASD showed a significant improvement in their judgments of the intensity of facial expressions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that self‐selected colored tints improved judgments of the intensity of facial expressions for individuals with ASD but not for TD individuals, in line with the findings of Ludlow et al []. In contrast to TD individuals, whose judgments were (non‐significantly) poorer when colored tints were added to faces, individuals with ASD showed a significant improvement in their judgments of the intensity of facial expressions.…”
Section: Discussionsupporting
confidence: 89%
“…The benefits of colored overlays have also been documented for complex emotions. In a paper version of the “Reading the Mind in the Eyes” task [Baron‐Cohen & Cross, ], Ludlow et al, [] demonstrated an improvement in the classification of facial emotional expressions from the eye area, in individuals with ASD, using colored overlays. A single case study of an individual with ASD showed an improvement in social and communication abilities when individually tinted colored glasses were worn [Ludlow & Wilkins, ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Ludlow et al, 2006, 2008, 2012) found, in clinical settings, a perceptual benefit from the use of colored filters in a large proportion of individuals with ASD. The overlays were designed to sample chromaticity systematically and comprehensively so that if there was any color that was beneficial, there was an available overlay or combination of overlays providing a close approximation to this color.…”
Section: Introductionmentioning
confidence: 91%
“…The findings suggested using colours combined with training methods to improve different levels of visual function in ASD. For example, coloured filters showed improved performance in individuals with ASD on visual perception, social tasks and reading . The proposed mechanism is that coloured filters reduce cortical hyperexcitation, increased by the cortical noise in ASD, especially in primary sensory cortices.…”
Section: Visual Impairments In Asdmentioning
confidence: 99%